The Effect of Good Corporate Governance and Firm Characteristics on Firm Value of Sharia and Conventional Banks in Indonesia - Soliyah Wulandari; Dede Sudirja; Rezky Mehta Setiadi; Haezah Nur Shabrina (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2025)
This research aims to empirically prove the influence of good corporate governance and company characteristics on firm value. Good corporate governance in question is the board of directors, independent commissioners, audit committee, and institutional ownership, while company characteristics are company size, profitability, and leverage.Â The object of this research is Banks Listed on the Indonesian Stock Exchange. The sample period in this research is 2021 and 2022. Sample selection was carried out using the purposive sampling method. The final sample used in this research was 60 observations. The secondary data collected were financial reports from each bank. The data was processed using multiple regression model statistical tests. The results of this research show that company size and profitability influence the firm value of sharia and conventional banks listed on the Indonesia Stock Exchange. Meanwhile, the board of directors, independent commissioners, audit committee, institutional ownership, and leverage have no effect on the firm value of sharia and conventional banks listed on the Indonesia Stock Exchange.